Selective loss of a DNase I hypersensitive site upstream of the tyrosine aminotransferase gene in mice homozygous for lethal albino deletions. - Zaret, K S (1992)
Several overlapping chromosomal deletions spanning the albino locus in the mouse cause perinatal lethality when homozygous and a block in the transcriptional induction of various unlinked hepatocyte-specific genes. Studies of such lethal albino deletion homozygotes in perinatal stages revealed a deficiency in the transcriptional inducibility of the tyrosine aminotransferase (TAT) gene by glucocorticoids; yet, glucocorticoid receptor and hormone levels were shown to be unaffected. To identify a molecular defect underlying the failure of inducible expression, we examined the chromatin structure of the TAT gene. Whereas in wild-type animals the TAT promoter becomes DNase I hypersensitive at birth, such hypersensitivity fails to develop in lethal albino deletion homozygotes. By contrast, the deletions do not affect the appearance of three DNase I-hypersensitive sites upstream of the TAT promoter in the liver, nor do they affect two hypersensitive sites upstream of the expressed alpha-fetoprotein gene. These findings demonstrate that the abnormality of chromatin structure identified in lethal albino deletion homozygotes occurs on a highly selective basis. Specifically, normal differentiation of the TAT promoter chromatin appears to depend directly or indirectly on the action and product of a gene mapping within the deleted region.